The effects of staphylococcal protein A on human lymphokine-activated killer cell induction - Lindemann, R A; Singh, K P; Shau, H; Gupta, R K (Cancer immunology, immunotherapy : CII, 1991)
Staphylococcal protein A (Cowan strain; SpA), a biologically active molecule capable of inducing augmented natural killer (NK) cell cytotoxicity, was studied in regard to its effects on lymphokine-activated killer (LAK) cell development. SpA, when co-cultured with interleukin-2 (IL-2) for 4 days, significantly augmented both LAK activity against NK-resistant M14 (melanoma) target cells and DNA synthesis of peripheral blood mononuclear cells (PBMC). This enhancement occurred with SpA concentrations of 1-100 micrograms/ml in a dose-dependent fashion; concentrations above 100 micrograms/ml were no more effective. When SpA (10 micrograms/ml) was added to PBMC cultures with various IL-2 concentrations, cytotoxicity was increased over controls with IL-2 alone. The peak cytotoxic effect reached a plateau at 80 U/ml IL-2. SpA alone induced early (day 1) cytotoxicity, which rapidly declined. SpA alone did not induce PBMC proliferation but it did increase expression of CD25 (Tac), IL-2 receptor alpha chain, on CD56(Leu19)-positive and -negative cells. The potentiating effect of SpA was significantly enhanced in serum-free medium. If either human AB serum or human IgG was added to cultures SpA-enhanced LAK cytotoxicity was diminished. The addition of anti-interferon gamma (anti-IFN gamma) antibody, but not anti-IFN alpha, inhibited (SpA+IL-2)-induced cytotoxicity, indicating that IFN gamma is partially responsible for the additive cytotoxic effect.